The Comparison of Pipe Thickness Selection Method Using Full Flange Rating and non-Full Flange Rating of Cryogenic Services in an LNG Plant Construction - Agustar, Ari; Iskandar, Isdaryanto; Putra, Wahyuaji Narottama (Journal of Materials Exploration and Findings, 2022)
Significant growth of gas demand as a source of power generation for domestic use and industries, mainly in the developed countries, has forced the effort to secure the gas supplies located thousands of miles away across the sea as an economical way of gas transportation instead of transporting by pipeline. LNG technology was created as the solution. Natural gas is refrigerated below its boiling point (-160oC to -162oC), known as cryogenic temperature or cryogenic service. Material of Construction (MOC) selection report showed that 304/304L and 316/316L Stainless Steel pipe could withstand and be suitable for this type of service. However, the SS pipe price could be much more costly than the CS pipe. An alternative philosophy to the full-flange rating is introduced in this paper to reduce SS pipe thickness without sacrificing safety issues and proper engineering practice. The philosophy of the pipe wall-thickness calculation method utilized in this paper showed no impact on the class 150 rating due to the selected thicknesses being equal or higher. However, the class 300 rating successfully reduced pipe selected thickness for pipe sizes larger than 24 inches ranging from 20,15% to 31,1%, and for class 600 rating successfully reduced the thickness ranging from 6,28% to 16,55% for pipe sizes 10 inches and larger. The overall pipe thickness reduction reduced pipe weight for cryogenic services by approximately 91,84 tons. The philosophy of the pipe wall-thickness calculation method for cryogenic services can be extended to all other services in the entire LNG production train to gain maximum cost savings for the pipe purchasing cost.